Growth Of Freshwater Pomfret Fish (Collosoma macropumum) In A Recirculation System With A Horizontal Filter - Rafiah, Siti; Junaidi, Muhammad; Diniarti, Nanda (Indonesian Journal of Aquaculture Medium, 2024)
<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">Fish<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;"> farming <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">is <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">one <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">of <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">the <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">activities <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">to <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">meet <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">the <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">food <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">needs <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">of <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">the <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">fisheries <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">sector<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">, <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">one <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">of<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">which <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">is <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">freshwater <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">fish <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">cultivation <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">which <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">gets <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">very <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">high <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">economic <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">value <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">so <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">that <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">freshwater<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">pomfret <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">fish <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">from <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">year <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">to <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">year <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">increases<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">. <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">Although <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">this <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">fish <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">is <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">rarely <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">consumed<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">, <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">freshwater<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">pomfret <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">fish <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">is<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;"> a <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">product <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">that <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">is <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">quite<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;"> in <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">demand<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">. The <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">recirculation <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">system <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">is <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">an <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">application<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">option <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">to <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">control <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">the <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">quality <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">of <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">water <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">that <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">passes <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">through<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;"> a filter. <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">This<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;"> study <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">aims <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">to <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">analyze<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">the <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">growth <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">of <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">freshwater <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">pomfret <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">fish<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;"> (<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">Collosoma <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">macropomum<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">) in<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;"> a recirculation system with a horizontal filter<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">. <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">This <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">research <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">was <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">carried <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">out <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">for<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;"> 50 <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">days<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">, <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">at <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">the <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">Fish <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">Production <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">and<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">Reproduction <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">Laboratory<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">, <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">University <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">of<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;"> Mataram <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">using <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">an <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">experimental <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">method <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">using<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;"> a <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">Complete<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;"> Design (RAL) <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">consisting <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">of<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;"> 4 <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">treatments <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">and<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;"> 3 <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">replicates <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">where <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">there<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;"> were 12 <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">experimental <span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">units<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">.<span class="s15" style="line-height: 14.4px; font-size: 12px; font-family: Cambria; caret-color: #000000; color: #000000; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;"> The test parameters include growth rate (absolute length, specific length, absolute weight and specific weight), feed conversion ratio (FCR), survival (SR) and water quality. The data was analyzed using Analysis of Variance (ANOVA) and continued with the Duncan test. The results showed that the test parameters included growth rate (absolute length, specific length, absolute weight and specific weight), feed conversion ratio (FCR), survival (SR) and the best water quality were found in P3 with a growth rate (absolute length of 7 cm, specific length of 0.033 %/day, absolute weight of 24.5 grams and specific weight of 0.053%/day), feed conversion ratio (FCR) of 1.1, survival (SR) of 90% and water quality (temperature of 29-30 °C, Dissolved Oxygen (DO) of 3-6 mg/L and pH of 7-8).